Angiolymphoid Hyperplasia With Eosinophilia - Chatterjee Gobinda (Indian Journal of Dermatology, 2000)
A patient with nodular swelling over scalp in presented. The histopathology of the lesion is consistent with angiolymphoid hyperplasia with eosinophilia. The subtle differences form Kimuraâ€s diseases are discussed.